2021
DOI: 10.1038/s41598-021-84022-1
|View full text |Cite
|
Sign up to set email alerts
|

Role of sex in the association between childhood socioeconomic position and cognitive ageing in later life

Abstract: We aimed to explore sex differences in the association of childhood socioeconomic position (SEP) with the level of cognitive performance and the rate of cognitive decline. We studied 84,059 individuals (55% women; mean age 64 years) from the Survey on Health, Ageing and Retirement in Europe. Sex differences in the association of childhood SEP (household characteristics at age 10) with the level of cognitive performance (verbal fluency, immediate recall, delayed recall) were analysed using multilevel linear reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…The interaction models presented here suggest that higher-IEO contexts may prevent women, particularly from lower educated backgrounds who are at increased risk to not receive skill-matching education, to reach their full cognitive potential. The models incorporating childhood information showed that women schooled in higher-IEO contexts and who had less advantaged parental socioeconomic backgrounds had steeper cognitive decline, confirming and extending recent findings ( Wolfova et al, 2021 ). Further, several studies link changes in educational system to changes in gender egalitarianism ( Shu, 2004 ; Thijs et al, 2019 ).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The interaction models presented here suggest that higher-IEO contexts may prevent women, particularly from lower educated backgrounds who are at increased risk to not receive skill-matching education, to reach their full cognitive potential. The models incorporating childhood information showed that women schooled in higher-IEO contexts and who had less advantaged parental socioeconomic backgrounds had steeper cognitive decline, confirming and extending recent findings ( Wolfova et al, 2021 ). Further, several studies link changes in educational system to changes in gender egalitarianism ( Shu, 2004 ; Thijs et al, 2019 ).…”
Section: Discussionsupporting
confidence: 86%
“…If anything, women showed greater resilience to cognitive aging than men ( McCarrey et al, 2016 ). However, effects of early-life socioeconomic disadvantage on cognitive performance have been shown to be greater for women than men ( Wolfova et al, 2021 ). In this study, we observed that the association of level of IEO with rate of cognitive decline differed between the sexes: Associations of level of IEO with rate of cognitive decline were largely absent in men, whereas women showed steeper decline in two measures of cognitive performance, delayed recall and verbal fluency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, main effect results supported that participants with less educated mothers (i.e., less than secondary school mother education) showed an increase in cognitive decline between the ages of 69.8 and 76.7 years of age ( β = −0.132, p = 0.048, and CI = −0.80, −0.00). As a recent study showed that low childhood SES had a greater association to cognitive decline in women ( N = 84,059; Mage = 64.0 years; Wolfova et al, 2021 ), we analyzed gender as a possible moderator between participants with less educated mothers and cognitive decline. Results showed no interaction between gender and less educated mothers within our analytical sample ( β = −0.001, CI = −0.529, 0.522).…”
Section: Resultsmentioning
confidence: 99%
“…Evidence suggests that people in low SEPs may be less able to take advantage of developing health information because of limited access to the information and limited means to adapt to new information (Finkel & Ernsth Bravell, 2020; Mirowsky & Ross, 2003). As a result of these factors, people with low SEP tend to have worse cognitive and physical function in late adulthood (Darin-Mattsson et al, 2017; Wolfova et al, 2021).…”
mentioning
confidence: 99%